The Role of Management Accounting : It's Implementation In The Public Sector - Sabeni, Arifin (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 1999)
Many definitions of management accounting exist, and although these lack of complete agreement, it is possible to say that management accounting plays important roles in an organization. Particularly, it plays in the managerial tasks of planning, controlling, and decisionmaking. All organizations need to make decisions and need to plan and control their activities, and all organizations, whether they be in the private or the public sector, ought to be able to benefit from the use of such management accounting techniques. However, the management accounting literature and the development of the techniques of management accounting are almost exclusively concerned with a private sector environment. Little discussions are placed on the public sector environment. For this reason, the purpose of this paper is to discuss the role and operation of management accounting in the public sector. In so doing, this paper; firstly, discusses the role of management accounting in an organization, then, the role and operation of management accounting in the public sector. After that, in order to give a comparison between theory and practice, this paper describes the actual practice of the role and operation of management accounting in the New South Wales Department of Education as an illustration. Furthermore, such evaluation of management accounting practices in the public sector are dis cussed; andfinally; summary and conclusion.